4
$\begingroup$

If $K$ is finite field, then one can easily show that there is no proper subring $R$ with $Q(R) = K$, where $Q(R)$ is the field of fractions of $R$. As a consequence, algebraic extensions $K$ of finite fields have no subring $R$ with $Q(R) = K$.

If $K / \mathbb{Q}$ is an algebraic extension, we have $Q(R) = K$ for the ring $$ R := \{ x \in K : \exists f \in \mathbb{Z}[X] \text{ normed }, f(x) = 0\}.$$ In a more general way, if $L / K = Q(S)$ is an algebraic extension, then the similarly defined ring $$R := S^L := \{ x \in L : \exists f \in S[X] \text{ normed }, f(x) = 0\}$$ satisfies $Q(R) = L$. Moreover $R$ is integrally closed (every zero $x \in L$ of normed polynomials $f \in S[X]$ is already in $R$) and $R$ is a field if and only if $S$ is a field.

Since purely transcendental field extensions are quotient fields of proper subrings by definition, we see that every field except the algebraic field extensions of finite fields can be written as $K = Q(R)$ with a proper subring $R \subseteq K$.

I now wonder if there is some kind of inverse of this procedure.

Let $L/K$ be an algebraic field extension with $Q(R) = L$. We assume that $R$ is integrally closed. We define $R_K := R \cap K$. Then $R_K$ is again an integral domain as an intersection of integral domains. But what do we know about $Q(R_K)$? Is it equal to $K$ or is the extension $K / Q(R_K)$ at least algebraic? Do we have $(R_K)^L = R$?

If $K / Q(R_K)$ is algebraic we have the inclusion $(R_K)^L \subseteq R$ (which is kind of obvious) and we again have that $R$ is a field (so $R = L$) if and only if $R_K$ is a field. Maybe closely related is the question, if there is a smallest integral domain $R \subseteq L$ with $Q(R) = L$.

$\endgroup$
1
+50
$\begingroup$

Let $R=k[X]$ and $L=k(X)$, $k$ a field. Now consider the subfield $K=k(X+\dfrac{1}{X})$. Then $$R\cap K=k(X+\dfrac{1}{X})\cap k[X]=k.$$

Let $f,g,h\in k[X]$ such that $$\dfrac{f(X+\dfrac{1}{X})}{g(X+\dfrac{1}{X})}=h(X).$$ Set $m=\deg f$ and $n=\deg g$. Then we have $$\dfrac{X^mf(X+\dfrac{1}{X})}{X^ng(X+\dfrac{1}{X})}=X^{m-n}h(X).$$ Set $f_1(X)=X^mf(X+\dfrac{1}{X})$ and $g_1(X)=X^ng(X+\dfrac{1}{X})$. We have $f_1,g_1\in k[X]$, $\deg f_1=2m$, $\deg g_1=2n$, and moreover, $\gcd(X,f_1(X))=\gcd(X,g_1(X))=1$. From $$\dfrac{f_1(X)}{g_1(X)}=X^{m-n}h(X)$$ we get $m=n$ if $m\ge n$, and therefore $\deg h=0$, or $X^{n-m}f_1(X)=g_1(X)h(X)$ if $n>m$, and then $h(X)=X^{n-m}h_1(X)$, so $f_1(X)=g_1(X)h_1(X)$, a (degree) contradiction.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Are you sure about the last assertion? At least I don't see it. $\endgroup$ – Paul K Jan 12 '16 at 9:38
  • $\begingroup$ One last thing (maybe I'm just stupid again): $h_1(X) = h(X) X^{m - n}$. Why is $h_1 \in k[X]$? Otherwise I don't see the degree contradiction. $\endgroup$ – Paul K Jan 12 '16 at 18:05
  • $\begingroup$ @menag If $X^{n-m}\mid g_1(X)h(X)$ and $\gcd(X,g_1(X))=1$, then what you get? $\endgroup$ – user26857 Jan 12 '16 at 20:22

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.